Interception at a Crossroads: Juridical and Strategic Perspectives on Wiretapping in Indonesia’s Counter-Terrorism Framework in the Digital Era - Artya, Ade; Priyanto, Sapto; Subandi, Imam (Journal of Law, Politic and Humanities, 2025)
This research investigates the critical crossroads in Indonesia's counter-terrorism strategy, where success in suppressing terrorist attacks coincides with the expansion of a dual surveillance apparatus in the digital era. Employing a qualitative approach with juridical normative analysis and the Actor-Network Theory (ANT) framework, this study examines the strategic and legal dimensions of wiretapping. Findings indicate that the formal legal framework, particularly Law No. 5 of 2018, provides a basis for effective proactive interception but contains ambiguities that grant broad discretionary power. Crucially, the research uncovers a parallel, unregulated surveillance regime involving invasive spyware procurement and extra legal agreements that bypass judicial oversight, thereby threatening civil liberties. The study concludes that this duality creates a security paradox, where tactical success masks systemic risks to the rule of law. Comprehensive legislative reform is imperative to establish a singular, proportional, transparent, and accountable framework.